Within-week differences in external training load demands in elite volleyball players - Zeki Akyildiz; Henrique de Oliveira Castro; Erhan Çene; Lorenzo Laporta; Coskun Parim; Emre Altundag; Cengiz Akarçeşme; Giovanni Guidetti; Giovanni Miale; Ana Filipa Silva; Hadi Nobari; Filipe Manuel Clemente (BMC, 2022)
Abstract Purpose The aim of this study was to analyze the within-week differences in external training intensity in different microcycles considering different playing positions in women elite volleyball players. Methods The training and match data were collected during the 2020-2021 season, which included 10 friendly matches, 41 league matches and 11 champions league matches. The players' position, training/match duration, training/match load, local positioning system (LPS) total distance, LPS jumps, accelerations, decelerations, high metabolic load distance (HMLD), acute and chronic (AC) mean and AC ratio calculated with the rolling average (RA) method and the exponentially weighted moving average (EWMA) method, monotony and strain values were analyzed. Results All the variables except strain, Acc/Dec ratio and acute mean (RA) showed significant differences among distance to match days. Regarding the players' positions, the only difference was found in the AC ratio (EWMA); in all microcycles, the middle blocker player showed workload values when compared with the left hitter, setter and libero. Conclusion Overall, the analysis revealed that the intensity of all performance indicators, except for strain, acc/dec and acute mean load (RA), showed significant differences among distance to match day with moderate to large effect sizes. When comparing players' positions, the middle blocker accumulated the lowest loads. There were no significant differences among other positions.